Protective Properties of Novel S‐Acyl‐Glutathione Thioesters Against Ultraviolet‐induced Oxidative Stress. (1st October 2012) - Wright, Daniel; Zampagni, Mariagioia; Evangelisti, Elisa; Conti, Simona; D'Adamio, Giampiero; Goti, Andrea; Becatti, Matteo; Fiorillo, Claudia; Taddei, Niccolò; Cecchi, Cristina; Liguri, Gianfranco
Abstract UV‐induced toxicity is characterized by marked oxidative stress, accompanied by the depletion of key cellular antioxidants, particularly glutathione (GSH). Replenishing cellular GSH may represent a means of counteracting UV‐induced toxicity: however, treatment with free GSH is not therapeutically effective due to its unfavorable pharmacokinetic properties. In this study, we show that S‐acyl‐glutathione (acyl‐SG) derivatives, which consist of an acyl chain (of variable length and saturation) linked via a thioester bond to GSH, increase intracellular levels of reduced GSH in primary skin fibroblasts, adenocarcinoma HeLa and neuroblastoma SH‐SY5Y cells. Consistent with this, acyl‐SG derivatives protect against UV‐induced reactive oxygen species (ROS) production and UV‐B/C‐mediated lipid peroxidation and caspase‐3 activation in the analyzed cell lines, with unsaturated thioesters displaying a significantly greater protective effect. Taken together, our findings suggest that acyl‐SG thioesters may be therapeutically effective in the treatment of UV‐related skin disorders and oxidative stress‐mediated conditions in general.